Onset Time of Binocular Rivalry and Duration of Inter-Dominance Periods as Psychophysical Markers of ADHD. (January 2013) - Casanova, J Antonio Aznar; Campos, Juan Antonio Amador; Sánchez, Manuel Moreno; Supèr, Hans
Attention deficit hyperactivity disorder (ADHD) is one of the main neurobiological disorders in young children. Despite its prevalence, current diagnosis is debated. In this study we tested whether measures of binocular rivalry (BR) can contribute to the diagnosis of ADHD. BR is a phenomenon that is produced when two different images are presented to the two eyes simultaneously. Under these conditions the image presented to one eye competes with that presented to the other eye in seeking to achieve perceptual dominance. This competition is resolved through the activation of a given percept coupled with the suppression of the percept that had predominated until that point. We assume that the difficulty with inhibiting responses of ADHD children also affects their ability to inhibit the dominant image in a BR context. We analyzed the time to rivalry onset and the inter-dominance periods as measures of the temporal cost of resolving how long it takes for the brain to select (or suppress) one percept over the other. Our results show that the time to onset of rivalry (the first dominance) was longer in the clinical groups (ADHD-C and ADHD-I) than in the control group. As regards the inter-dominance periods, these were longer in the ADHD-C group than among controls, with the shortest period corresponding to the ADHD-I group. This study shows that BR can be used as a tool to develop a behavioral indicator of ADHD.